"The Line’s Getting Mighty Blurry": Politics, Polemics and Performance in The Noam Chomsky Lectures - Coulthard, Lisa (Studies in Canadian Literature, 1995)
Daniel Brooks and Guillermo Verdecchia state that The Noam Chomsky Lectures is a course, based on the political writings of Noam Chomsky, in intellectual self-defence and semiological guerilla warfare, which gives the audience the tools to resist the manipulation and control exerted by mass media. However, Brooks and Verdecchia, and Chomsky himself, do not question the "transmitter-message-receiver" model of communication. The play maintains the audience-performer division of power and sets up the performers as "provos of Critical reception," thereby failing in its appointed task.